Cyclotron production of no carrier added 186gRe radionuclide for theranostic applications. (December 2020) - Khandaker, Mayeen Uddin; Nagatsu, Kotaro; Minegishi, Katsuyuki; Zhang, Ming-Rong; Jalilian, Amir R.; Bradley, D.A.
Abstract: 186g Re ( T 1/2  = 3.7183 d, E (β − )mean  = 346.7 keV, I (β − )mean  = 92.59%), a mixed beta and γ-emitter shows great potential for use in theranostic applications. The dominant 185 Re(n, γ) route, via use of a nuclear reactor, provides 186g Re in carrier added form with low specific activity, while cyclotrons offer no carrier-added (NCA) high specific activity production of 186g Re. However, to be able to select the best possible nuclear reaction and to optimize the production route via the use of a cyclotron, information on the excitation function for the reaction of interest as well as for the competing reactions is necessary. Accordingly, we have conducted a detailed study of the excitation functions for nat W(d, x) reactions in seeking optimized parameters for the NCA production of 186g Re. Noting a discrepancy among the experimental data, we made an evaluation of the available literature, finally selecting optimum parameters for the production of 186g Re via the 186 W(d, 2n) 186 Re reaction. These beam parameters were then used for batch production of 186g Re by irradiating an enriched 186 W metallic powder target, followed by a subsequent automated chemical separation process. The preliminary results show 98.1% radionuclidic purity of 186g Re at 8 h subsequent to the End of Bombardment (EOB), offering the potential for use in clinical applications. Highlights: A brief review on production routes for theranostic 186g Re has been presented. 186 W(d, 2n) 186g Re shows the best route for NCA production of 186g Re. Highly enriched 186 W metallic powder was activated for 2 h by 20 MeV deuteron. An automated chemical separation process at NIRS hot chemistry lab was used. 98.1% radionuclidic purity of 186g Re was obtained at 8 h after EOB.